Sentence Representation In Context-Sensitive Grammars - Seljan, Sanja (Array, 2002)
Every language, whether it is natural or artificial, has its recognizable grammar that consists of allowed elements and rules for putting those elements together. The main aim of the formal grammar is to represent rules for generation of the artificial or natural languages. While artificial languages (such as note system, logic, mathematics, programming languages) are described by context-free formal grammar aiming to describe syntax, natural languages tend to be described by context-sensitive rules aiming to include, as much as possible, syntactic and semantic component. Among many formal grammars that tend to describe as much as possible the natural language sentences, in this paper two context-sensitive grammars will be presented: Lexical-Functional Grammar and Case Grammar that aim to include semantic roles (such as agent, theme, beneficiary, goal, location, etc.) in order to represent the natural language sentences.